De-policing as a result of public scrutiny: examining officers’ perceptions of negative media attention and willingness to engage in self-initiated activity - Gau, Jacinta M. (Journal of crime and justice, 2022)
With police facing constant negative publicity, concerns have been raised that officers working the street will draw back on their efforts. Prior research relying on official data has not found increases in crime as a result of this so-called Ferguson or de-policing effect. In the present study, it is argued that officers’ own reported willingness to initiate proactive enforcement activities should be added to this body of research. If there is a Ferguson effect, it most likely exists in the realm of high-discretion, low-visibility decision making. Data are from surveys administered in-person to officers in a large, urban department. Results show that officers who perceive higher levels of negative publicity feel that police are less likely to self-initiate stops. Those who feared being filmed unfairly also reported reluctance among their colleagues. Perceptions of being supported by top management appeared to be a protective factor, with those experiencing strong support from managers reporting less concern about self-initiated enforcement. Findings support the existence of a de-policing or Ferguson effect insofar as intense scrutiny from the public and media appear to discourage some officers from initiating proactive stops. This indicates that when de-policing occurs, it is likely concentrated among high-discretion, low-visibility decisions.